Erratum Corrigendum : The Effect Of Therapeutic Communication On The Level Of Self-Esteem In The Elderly: A Case Study Of The Laut Dendang Village In The Percut Sei Tuan District - Pasaribu, Masdalifa; Lubis, Zulfahri; Siregar, Muhammad Kevin Humala Sakti; Fitria, Aida; Ma’ruf, Amar (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Self-esteem is an individual's self-evaluation that expresses approval or disapproval and identifies the level of individual confidence in their abilities, meaningfulness, success, and self-worth, while therapeutic communication plays a role in helping solve problems, healing, clarifying and reducing emotional and mental burdens, and helping to take effective action for patients. The purpose of this study was to determine the effect of therapeutic communication on the level of self-esteem in the elderly in Laut Dendang Village, Percut Sei Tuan District. This study used a quasi-experimental method (pretest-posttest). The study population was 62 people. The sample was taken using purposive sampling as many as 17 respondents. The results of the Paired T-test test showed the effect of therapeutic communication on the level of self-esteem in the elderly in Laut Dendang Village, Percut Sei Tuan District. The results of data analysis show a p-value of 0.000 with p ≤ 0.05 and a mean value (2.100). There was an increase of 2.1% after the intervention. In conclusion, there is an effect of therapeutic communication on the level of self-esteem in the elderly in Laut Dendang Village, Percut Sei Tuan District. This communication greatly affects self-confidence values related to feelings of weakness and helplessness